PENGARUH PEMBERIAN REBUSAN DAUN KATUK TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU MENYUSUI - Nasution, Naimah; Insani, Septa Dwi; Sayekti, Palupi Bodro; Ginting, Ria Nita (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2024)
Abstract Breast milk is the ideal food for babies because it provides all the energy and nutrients what they need in early life. The World Health Organization (WHO) and the United Nations Children's Fund UNICEF recommend that babies start breastfeeding within the first hour of birth and continue breastfeeding exclusively. The study examines the effect of Katuk leaf decoction on increasing breast milk production in lactating mothers who attended the Pera Independent Practical Midwifery Clinic in Medan Tuntungan District, Deli Serdang, in 2024. This study uses a quasi-experimental design using a single Group Pre Test-Post Test Design approach that does not use a control group; instead, the intervention is preceded by a pre-test followed by a post-test to assess change. According to the Wilcoxon signed rank test, the Z value was found to be 0.211 with a significance level of p=0.01 or less than 0.05 as a predetermined threshold indicating that breast milk production increased by an average of 9.30 after boiling katuk leaves. This result leads to the rejection of H0 and the acceptance of Ha, indicating that the findings support the effect of Katuk leaf decoction on increasing breast milk production in lactating mothers at Pera Independent Practice Midwifery Clinic, Tuntungan District, Medan, Deli Serdang, in 2024.